Reducing start-up costs for New Firms: The double dividend on the labor market - Uwe Dulleck; Paul Frijters; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2003)
Starting a firm with expansive potential is an option for educated and high-skilled workers. This option serves as an insurance against unemployment caused by labor market frictions and hence increases the incentives for education. We show within a matching model that reducing the start-up costs for new firms results in higher take-up rates of education. It also leads, through a thick-market externality, to higher rates of job creation for high-skilled labor as well as average match productivity. We provide empirical evidence to support our argument.
Keywords: J24; D73; J68; 330; Matching; Education; Start-up costs; Venture capital; Bureaucratic hurdles; Unternehmensgründung; Folgekosten; Risikokapital; Bildungsinvestition; Hochqualifizierte Arbeitskräfte; Arbeitsnachfrage; Theorie; Welt